2008
DOI: 10.1186/1471-2202-9-70
|View full text |Cite
|
Sign up to set email alerts
|

The function of Shp2 tyrosine phosphatase in the dispersal of acetylcholine receptor clusters

Abstract: BackgroundA crucial event in the development of the vertebrate neuromuscular junction (NMJ) is the postsynaptic enrichment of muscle acetylcholine (ACh) receptors (AChRs). This process involves two distinct steps: the local clustering of AChRs at synapses, which depends on the activation of the muscle-specific receptor tyrosine kinase MuSK by neural agrin, and the global dispersal of aneural or "pre-patterned" AChR aggregates, which is triggered by ACh or by synaptogenic stimuli. We and others have previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…However, we have not directly measured the effects of sub-maximal concentrations of n-agrin (with and without neuregulin-1) upon Shp2 activity in embryonic muscle cells. In addition, other studies have shown that NSC-87877, in the concentration range of 0.2-1 mM might also inhibit Shp1 (Qian et al, 2008). Further studies are needed to clarify the mode of this proposed inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we have not directly measured the effects of sub-maximal concentrations of n-agrin (with and without neuregulin-1) upon Shp2 activity in embryonic muscle cells. In addition, other studies have shown that NSC-87877, in the concentration range of 0.2-1 mM might also inhibit Shp1 (Qian et al, 2008). Further studies are needed to clarify the mode of this proposed inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Cdk5 and Shp2) involved in stabilizing AChR clusters (Fu et al, 2005;Ip et al, 2000;Lacazette et al, 2003;Lin et al, 2005;Qian et al, 2008;Zhao et al, 2007). There is reason to think that n-agrin-MuSK and neuregulin-1-ErbB signalling pathways converge to modulate AChR clustering (Chen et al, 2007;Lin et al, 2005;Ngo et al, 2004;Ngo et al, 2007;Qian et al, 2008;Zhao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Inhibition of cellular Shp2 activity by NSC-87877 has been reported in certain cells, including epithelial/carcinoma cells, fibroblasts, endothelial cells, muscle cells, and neuronal/glioma cells [17, 28, 29, 32, 33]. Using a biology-oriented synthesis approach, Nören-Müller et al [34] discovered a tetrazolefurofuran Shp2 inhibitor furanofuran-2a (sFig.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of AChR clustering can be altered by the level of activation (phosphorylation) of MuSK, with Ab1 kinases acting to increase the level of MuSK phosphorylation and consequently lead to more AChR clustering (Mittaud et al, 2004). More recently, Ngo et al (2012) (Madhavan & Peng, 2005;Madhavan et al, 2005;Qian et al, 2008). Both MuSK and the receptor associated protein, rapsyn are required for the clustering of AChR at the postsynaptic membrane Qu et al, 1996;Lin et al, 2001;Sanes & Lichtman, 2001).…”
Section: The Postsynaptic Membranementioning
confidence: 99%